Case Report: Next-generation metagenomic sequencing in the diagnosis of Brucella-associated joint infections—a case series analysis and comprehensive literature review - Duan, Jing; Li, Xianzeng; Hu, Yanhui; Pang, Feng; Cao, Yinguang; You, Zhiqing (Frontiers in Medicine, 2025)
BackgroundThe application of next-generation metagenomic sequencing (mNGS) in the diagnosis of human brucellosis, particularly in cases of joint brucellosis infection, remains under-explored, with rarely no case reports available in the literature. We present the first case series focusing on the application of mNGS in the diagnosis of Brucella joint infections. The results indicate that mNGS plays a crucial role in diagnosing Brucella joint infections, serving as a valuable complement, particularly for culture-negative patients.Case presentationThis study presents a comprehensive analysis of four cases of human joint brucellosis diagnosed using mNGS on the BGI sequencing platform, involving three male and one female patients aged from 42 to 63 years, all of whom had documented epidemiological exposure histories. mNGS successfully identified Brucella sequences in all cases, with additional diagnostic findings including a positive Brucella agglutination test in Patient 1, positive joint fluid cultures in Patients 3 and 4, and no positive results in Patient 2. Following surgery and targeted antibiotic therapy, all patients exhibited clinical improvement and favorable follow-up outcomes.ConclusionThese findings underscore the utility of mNGS as a critical diagnostic tool for joint brucellosis infections and highlight its potential as a complementary approach in cases of culture-negative joint infections. In cases where clinical suspicion of joint infection persists despite the absence of identifiable etiological evidence, the implementation of mNGS is strongly advised to facilitate timely and accurate clinical decision-making.